A tantalum-niobium carbide ceramic-palladium composite foil
Patent Information
- Application Number
- CN202511927333.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的是提供一种钽-碳化铌陶瓷-钯复合材料箔材及其制备方法和在氢气分离中的应用,该复合材料箔材兼具良好的结构稳定性、抗氢脆性能及高透氢选择性,具有较好的氢气传输效率和力学性能稳定性,可以作为高纯氢气分离场景中的核心分离材料,能够有效解决现有钯膜价格高、易发生氢脆,以及钽金属易形成氢化物导致力学性能下降、阻碍透氢膜应用的问题
1、本发明采用具有氢气高扩散性能的BCC钽金属作为复合材料基底,可以为氢气在复合材料内部的传输提供基础保障,确保材料具备核心透氢能力,满足氢气分离场景对透氢效率的基本需求。
Smart Images

Figure CN122979839A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen energy technology, and in particular to a tantalum-niobium carbide ceramic-palladium composite foil. Background Technology
[0002] Hydrogen fuel cells hold a crucial position in the energy sector. Compared to internal combustion engines, they reduce noise and heat generation, and compared to lithium-ion batteries, they significantly extend driving range. Hydrogen plays a decisive role in the widespread application of hydrogen fuel cells and other hydrogen energy sources. my country's annual hydrogen production is approximately 25 million tons, accounting for one-third of the world's total. However, to achieve safe and efficient utilization, there is an urgent need to improve hydrogen storage, transportation, and purification technologies.
[0003] As an upstream component of fuel cells, hydrogen energy supports the rapid development of the fuel cell industry. However, hydrogen purity significantly restricts fuel cell development. The main impurities in hydrogen include N2, O2, H2S, SO2, CH4, CO, CO2, NH3, and Cl2. Among these, N2 and CO2 lower the partial pressure of H2, hindering hydrogen diffusion to the membrane electrode assembly (MEA). Sulfur adsorption of H2S on the Pt surface replaces H, occupying original active sites and causing an irreversible and continuous decline in battery performance. The multi-mode adsorption effects of SO2 are even more difficult to eliminate. NH4+ from the perfluorosulfonic acid membrane reaction weakens the membrane's acidity, leading to an irreversible reduction in H+ transfer capacity. However, since most of my country's hydrogen energy comes from fossil fuel production, resulting in high impurity content, hydrogen purification technology has become crucial for the efficient utilization of hydrogen energy. Breakthroughs in hydrogen purification technology will deepen hydrogen energy utilization and gradually realize the large-scale application of fuel cells, while also improving the utilization efficiency and level of hydrogen produced as a chemical byproduct. Currently, the main methods for high-purity hydrogen purification include low-temperature adsorption, low-temperature liquefaction, metal hydride hydrogen purification, membrane diffusion, hollow fiber membrane diffusion, and pressure swing adsorption. In practical applications, selecting a suitable hydrogen purification method requires consideration not only of the economics of the equipment but also of the process's flexibility and reliability, ease of capacity expansion, the hydrogen content of the feedstock, hydrogen purity requirements, and the impact of impurities on downstream equipment. Based on these considerations, membrane separation technology is one of the most commonly used industrial technologies. Palladium membranes, due to their good mechanical strength, relative chemical stability, and good selective permeability, have become the mainstream choice and have been commercialized. However, the high price and hydrogen embrittlement issues of palladium metal membranes in hydrogen permeation applications significantly hinder their application in the field of hydrogen purification.
[0004] A novel approach to replacing palladium membranes with non-precious metals has emerged, with tantalum attracting significant attention due to its superior hydrogen permeability and lower diffusion activation energy compared to palladium. However, tantalum is more prone to hydride formation and embrittlement than palladium, and its increased hydride formation under high hydrogen partial pressures leads to a decline in membrane mechanical properties, severely hindering its application in hydrogen permeation membranes. Summary of the Invention
[0005] The purpose of this invention is to provide a tantalum-niobium carbide ceramic-palladium composite foil, its preparation method, and its application in hydrogen separation. This composite foil has good structural stability, resistance to hydrogen embrittlement, and high hydrogen permeability selectivity. It has good hydrogen transport efficiency and mechanical property stability, and can be used as a core separation material in high-purity hydrogen separation scenarios. It can effectively solve the problems of high price and easy hydrogen embrittlement of existing palladium membranes, as well as the problem of tantalum metal easily forming hydrides, which leads to a decline in mechanical properties and hinders the application of hydrogen permeable membranes.
[0006] To achieve the above objectives, the present invention provides the following solution: A tantalum-niobium carbide ceramic-palladium composite foil, comprising: tantalum metal layer; The niobium carbide ceramic gradient layer is formed on both sides of the tantalum metal layer, the niobium carbide ceramic gradient layer having a porous structure; and a palladium catalyst layer is deposited on the surface of the niobium carbide ceramic gradient layer.
[0007] Furthermore, the tantalum metal layer has a purity of 99.90–99.99% and a thickness of 200–500 μm; the niobium carbide ceramic gradient layer has a thickness of 100–500 nm; and the palladium catalyst layer has a thickness of 100–300 nm.
[0008] Furthermore, the hydrogen permeability coefficient of the composite foil under conditions of 500°C and a pressure difference of 0.2 MPa is 5.0–7.0 × 10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0009] The present invention also provides a method for preparing the above-mentioned tantalum-niobium carbide ceramic-palladium composite foil, comprising the following steps: (1) Preparation of niobium carbide gradient ceramics, including: A niobium metal nanolayer is deposited on the surface of tantalum foil by magnetron sputtering, followed by heat treatment in an oxygen atmosphere to form a niobium oxide ceramic nanolayer; then a graphite layer is deposited on the surface of the niobium oxide ceramic; finally, a porous niobium carbide ceramic gradient layer is formed by heat treatment at 1200-1500℃ for 1-3 hours in a vacuum atmosphere with a heating rate of 1-5℃ / min. (2) Preparation of a palladium catalyst layer, including: The porous niobium carbide ceramic layer is subjected to plasma cleaning, and then a palladium layer is deposited on its surface by magnetron sputtering to form a palladium catalytic layer with a thickness of 100-300 nm, thereby obtaining the tantalum-niobium carbide ceramic-palladium composite foil.
[0010] Furthermore, in step (1), the thickness of the graphite layer is 100-500 nm.
[0011] The present invention also provides a material for hydrogen separation, comprising the tantalum-niobium carbide ceramic-palladium composite foil as described in any of the preceding claims, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by any of the preceding claims.
[0012] The present invention also provides the use of the tantalum-niobium carbide ceramic-palladium composite foil as described in any of the preceding claims, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by the preparation method described in any of the preceding claims, in the preparation of a purification membrane for hydrogen separation.
[0013] The embodiments described in this specification can achieve at least the following beneficial effects: 1. This invention uses BCC tantalum metal, which has high hydrogen diffusion performance, as the composite material substrate, which can provide a basic guarantee for the transmission of hydrogen inside the composite material, ensuring that the material has core hydrogen permeability and meeting the basic requirements for hydrogen permeability efficiency in hydrogen separation scenarios.
[0014] 2. This invention grows niobium carbide porous ceramics on the surface of BCC tantalum metal. This niobium carbide porous ceramic acts as a barrier layer between tantalum and palladium metals, effectively mitigating interfacial interactions that may occur during use, thereby significantly improving the service life of the composite material. Simultaneously, the niobium carbide ceramic itself possesses resistance to hydrogen embrittlement; the presence of this barrier layer directly enhances the overall hydrogen embrittlement resistance of the composite material, preventing performance degradation or structural damage due to hydrogen embrittlement in a hydrogen environment.
[0015] 3. In niobium carbide porous ceramics, the natural pores formed between niobium carbide particles can serve as dedicated channels for hydrogen transport. Without hindering hydrogen diffusion, this ensures that hydrogen can pass through the composite material stably and efficiently, further guaranteeing the material's hydrogen permeability. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments or prior art of this specification, the drawings used in the description of the embodiments or prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic composite material prepared in Example 1; Figure 2 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic-palladium composite material prepared in Example 1; Figure 3 This is the curve showing the relationship between the hydrogen permeability coefficient and pressure difference of the tantalum-niobium carbide ceramic-palladium composite foil prepared in Example 1; Figure 4 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic composite material prepared in Example 2; Figure 5 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic-palladium composite material prepared in Example 2; Figure 6 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic composite material prepared in Example 2; Figure 7 This is a scanning electron microscope image of the tantalum-niobium carbide ceramic-palladium composite material prepared in Example 3; Figure 8 This is the curve showing the relationship between the hydrogen permeability coefficient and pressure difference of the tantalum-niobium carbide ceramic-palladium composite foil prepared in Example 3; Figure 9 This is the curve showing the relationship between the hydrogen permeability coefficient and pressure difference of the tantalum-niobium carbide ceramic-palladium composite foil prepared in Example 3; Figure 10 A flowchart illustrating the preparation method of the tantalum-niobium carbide ceramic-palladium composite foil provided by the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art. The terms "comprising" and similar expressions used herein mean that the element or object preceding the word covers the element or object listed following the word and its equivalents, but do not exclude other elements or objects.
[0019] Preferred embodiments of the present invention will now be described in more detail. While preferred embodiments of the present invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products. In the following embodiments, unless otherwise explicitly stated, "%" refers to weight percentage.
[0020] To make the technical solution of the present invention easier to understand, the technical concept of the present invention will be described below. It should be noted that the technical concept here is also part of the technical solution of the present invention and does not constitute a limitation on the scope of protection of the technical solution of the present invention.
[0021] The tantalum-niobium carbide ceramic-palladium composite foil provided by this invention has a three-layer composite structure of "support-mass transfer-catalysis" consisting of a substrate, a barrier layer, and a catalytic layer. The substrate is a foil-shaped support framework made of high-purity tantalum metal; the barrier layer is a porous niobium carbide ceramic gradient layer formed on both sides of the tantalum metal layer and tightly attached to the substrate surface; and the catalytic layer is a palladium metal layer deposited on the surface of the niobium carbide ceramic gradient layer and completely covers the barrier layer.
[0022] The microstructure of the tantalum-niobium carbide ceramic-palladium composite foil provided in this application is determined by the characteristics of the raw materials used in its preparation. Each layer works synergistically to form a functional system adapted to hydrogen separation scenarios. Specifically, the tantalum metal layer provides stable mechanical support and basic hydrogen diffusion channels; the niobium carbide ceramic gradient layer blocks the interdiffusion of tantalum and palladium and constructs dedicated hydrogen transport pores; and the palladium catalytic layer accelerates hydrogen dissociation to improve hydrogen permeability. These three elements work together to achieve a synergistic effect of "support-mass transfer-catalysis".
[0023] The substrate is a tantalum metal layer with a purity of 99.90–99.99% and a thickness of 200–500 μm, exhibiting a foil-like structure. The tantalum metal layer, with its high hydrogen diffusion characteristics due to its BCC crystal structure, provides a basic channel for hydrogen transport within the composite material. Simultaneously, its mechanical strength supports the overall foil structure, preventing deformation during subsequent layer deposition and use.
[0024] The barrier layer is a niobium carbide ceramic gradient layer. This layer uniformly covers both sides of the tantalum metal layer with a porous structure and has a thickness of 100-500 nm. Its porous structure provides a dedicated channel for hydrogen transport. At the same time, as a barrier layer between the tantalum metal and the palladium catalyst layer, it effectively blocks the mutual diffusion between the two. Moreover, the hydrogen embrittlement resistance of the niobium carbide ceramic itself can significantly improve the overall hydrogen embrittlement resistance of the composite material and avoid the degradation of the material's mechanical properties under high hydrogen partial pressure.
[0025] The catalyst layer is a palladium catalyst layer, in which palladium metal is deposited in a dense layered structure on the surface of the niobium carbide ceramic gradient layer with a thickness of 100-300 nm. As a catalytic site for hydrogen dissociation, the palladium catalyst layer can accelerate the dissociation and adsorption of hydrogen molecules on the material surface. Combined with the porous mass transfer channels of the niobium carbide ceramic gradient layer and the diffusion capacity of the tantalum metal layer, the hydrogen permeation selectivity and efficiency of the composite material are improved.
[0026] On a macroscopic level, the tantalum-niobium carbide ceramic-palladium composite foil of the present invention is in the form of a continuous foil, which can be directly used as a core separation element in hydrogen purification scenarios and is adapted to the assembly requirements of hydrogen separation devices.
[0027] The hydrogen permeability coefficient of the tantalum-niobium carbide ceramic-palladium composite foil is 5.0–7.0 × 10⁻⁶ under conditions of 500 °C and a pressure difference of 0.2 MPa. -8 mol·m -1 ·s -1 ·Pa -0.5 The hydrogen permeability coefficient under conditions of 500℃ and a pressure difference of 0.6MPa is 8.0~10.0×10. -8 mol·m -1 ·s -1 ·Pa -0.5 It can meet the requirements of high-purity hydrogen separation for hydrogen permeability.
[0028] like Figure 10 As shown, the present invention also provides a method for preparing the above-mentioned tantalum-niobium carbide ceramic-palladium composite foil, comprising the following steps: (1) Preparation of niobium carbide gradient ceramics includes: depositing a niobium metal nanolayer on the surface of tantalum foil by magnetron sputtering, followed by heat treatment in an oxygen atmosphere to form a niobium oxide ceramic nanolayer; then depositing a graphite layer on the surface of the niobium oxide ceramic; and finally heat treating it in a vacuum atmosphere at 1200-1500℃ for 1-3 hours at a heating rate of 1-5℃ / min to form a porous niobium carbide ceramic gradient layer.
[0029] In this step, tantalum foil is used as a substrate, and niobium metal is deposited on its surface using magnetron sputtering. The aim is to construct a uniform niobium metal source layer on the tantalum foil surface, providing the necessary niobium element for the subsequent ceramization reaction. After deposition, a niobium metal nanolayer is formed on the tantalum foil surface. This layer needs to be continuous and uniform to ensure that the subsequent oxidation reaction can proceed fully and synchronously, avoiding defects in the niobium carbide layer due to the lack of local niobium source. Then, the tantalum foil with the deposited niobium metal nanolayer is placed in an oxygen atmosphere, and a heat treatment process is used to promote the oxidation reaction of the niobium metal. In this process, the oxygen atmosphere provides a sufficient oxygen source to ensure that the niobium metal can be completely converted into a ceramic state. Under the oxygen atmosphere and heat treatment conditions, the niobium metal undergoes an oxidation reaction to form a niobium oxide ceramic nanolayer. This layer adheres tightly to the surface of the tantalum foil, serving as a smooth substrate for subsequent graphite deposition, and its oxygen content will participate in the reaction in subsequent steps, creating conditions for the formation of a porous structure.
[0030] Then, using the niobium oxide ceramic nanolayer prepared in the previous sub-step as a deposition carrier, a graphite layer is deposited on its surface. The graphite layer serves as a carbon source reserve, providing sufficient carbon for the subsequent high-temperature carbonization reaction, ensuring the quantity and purity of niobium carbide. Simultaneously, its carbon will participate in the subsequent reduction reaction, influencing the formation of the final porous structure. During this process, the graphite layer must uniformly cover the surface of the niobium oxide ceramic nanolayer to avoid localized carbon source insufficiency, preventing incomplete carbonization and resulting in uneven composition or structural defects in the niobium carbide layer. Finally, a high-temperature heat treatment in a vacuum atmosphere is performed to form a porous niobium carbide ceramic gradient layer. Using a vacuum atmosphere avoids impurities in the air, such as nitrogen and oxygen, from interfering with the carbonization reaction, and also prevents the tantalum foil from being additionally oxidized at high temperatures, ensuring product purity.
[0031] (2) The preparation of palladium catalyst layer includes: plasma cleaning of the porous niobium carbide ceramic layer, followed by deposition of palladium layer on its surface by magnetron sputtering to form palladium catalyst layer with a thickness of 100-300 nm, thereby obtaining the tantalum-niobium carbide ceramic-palladium composite foil.
[0032] The purpose of plasma cleaning of the porous niobium carbide ceramic layer prepared in step (1) is to remove any impurities that may remain on the surface of the ceramic layer, such as graphite debris left after graphite deposition and carbonization in the previous step, and trace oxide residues produced by oxidation. If these impurities are not removed, they will directly affect the interfacial bonding strength between the subsequent palladium layer and the ceramic layer, and may even lead to defects such as local vacancies and pinholes in the palladium layer. After plasma cleaning, a palladium layer is deposited on the surface of the porous niobium carbide ceramic layer using magnetron sputtering. The magnetron sputtering deposition method can make palladium metal atoms uniformly distributed on the surface of the ceramic layer, which is particularly suitable for the surface morphology of the porous niobium carbide ceramic layer and avoids local uneven deposition caused by the porous structure of the ceramic layer.
[0033] Meanwhile, in step (1), the thickness of the graphite layer can be 100–500 nm to ensure that the niobium carbide ceramic gradient layer can be stably formed and possess the expected porous structure and properties. If the thickness of this layer is less than the lower limit, the oxygen in the niobium oxide may not be completely reduced, and the residual oxygen will combine with niobium to form non-target oxide impurities, reducing the purity of the niobium carbide ceramic layer. At the same time, niobium may not be fully converted into niobium carbide, and unreacted niobium will affect the mechanical properties and hydrogen embrittlement resistance of the ceramic layer, and may also cause the porous structure to be discontinuous, destroying the hydrogen transport channels. If the thickness of this layer is greater than the upper limit, the excess carbon source may result in excess carbon residue after vacuum high-temperature heat treatment. This residual carbon will adhere to the surface of the niobium carbide particles or fill the pores between the particles, blocking the porous structure that should serve as a hydrogen transport channel, directly reducing the hydrogen permeability efficiency of the subsequent composite material.
[0034] Example 1 Example 1 of the present invention prepares a tantalum-niobium carbide ceramic-palladium composite foil according to the following steps: (1) Preparation of niobium carbide gradient ceramics Tantalum foil with a purity of 99.9% and a thickness of 200 μm was first cleaned using a plasma surface cleaning device for 30 minutes to remove surface oil and oxide layers. Subsequently, niobium nanolayers were deposited on both surfaces of the tantalum foil using a magnetron sputtering device for 5 minutes to ensure uniform niobium coverage.
[0035] The tantalum foil with niobium metal nanolayers deposited was transferred to a tube furnace, and an oxygen atmosphere (oxygen flow rate of 50 mL / min) was introduced. The furnace was then heat-treated at 100 °C for 30 minutes to completely oxidize the niobium metal nanolayers, forming a niobium oxide ceramic nanolayer with a thickness of approximately 100–300 nm.
[0036] Next, graphite was deposited on the surface of the niobium oxide ceramic nanolayer using magnetron sputtering for 10 minutes to form a graphite layer (approximately 100-300 nm thick). This layer was then transferred to a vacuum tube furnace and heated to 1200°C at a rate of 1-5°C / min, holding for 1 hour for high-temperature heat treatment. During this heat treatment, oxygen was reduced to CO2 by carbon and released, while niobium reacted with carbon to form niobium carbide particles. Simultaneously, the volume shrinkage caused by the reaction of oxygen and carbon resulted in a porous structure, ultimately yielding a tantalum foil with a porous niobium carbide ceramic gradient layer on its surface.
[0037] Scanning electron microscope images of the obtained tantalum-niobium carbide ceramic composite material are shown below. Figure 1 As shown. Figure 1 In this composite material, the niobium carbide ceramic gradient layer exhibits a microstructure composed of numerous submicron-sized, interwoven morphological units. The particles are uniformly distributed, and these units form abundant pores with sizes ranging from 50 to 100 nm, falling within the submicron range. This creates a continuous porous network, and the niobium carbide ceramic gradient layer is approximately 100 to 300 nm thick, consistent with the design goals. This porous structure not only provides dedicated channels for hydrogen transport, ensuring efficient hydrogen mass transfer within the composite material, but the interwoven porous morphology also enhances the interfacial bonding between the niobium carbide ceramic gradient layer and the tantalum metal layer and palladium catalyst layer. This further enhances its role as a barrier layer, preventing the interdiffusion of tantalum and palladium. Furthermore, leveraging the inherent hydrogen embrittlement resistance of niobium carbide, the mechanical stability of the composite material under high hydrogen partial pressure conditions can be improved.
[0038] (2) Preparation of palladium catalyst layer The tantalum foil with niobium carbide ceramic gradient layer obtained in step (1) is placed in a plasma cleaner and argon gas (argon gas flow rate of 30 mL / min) is introduced for plasma cleaning for 10 minutes to remove residual graphite debris and impurities on the surface of niobium carbide.
[0039] Subsequently, palladium metal was deposited on the surface of the niobium carbide ceramic gradient layer using a magnetron sputtering device for 10 minutes to form a uniform palladium catalytic layer with a thickness of about 100 nm, and finally a tantalum-niobium carbide ceramic-palladium composite foil was obtained.
[0040] Scanning electron microscope images of the obtained tantalum-niobium carbide ceramic-palladium composite material are shown below. Figure 2 As shown. Figure 2 In the process, the palladium catalyst layer is tightly attached to the surface of the niobium carbide ceramic gradient layer, without obvious cracks or pores.
[0041] (3) Hydrogen permeability test of composite foil The prepared tantalum-niobium carbide ceramic-palladium composite foil was cut into circular samples with a diameter of 20 mm. The samples were then stacked and sealed in a hydrogen purifier (the sealing substrate was a graphite paper ring). A mixture of hydrogen and argon gas (with a hydrogen gas fraction of 90%) was introduced to test the hydrogen permeability.
[0042] Test conditions: Temperature 500℃, outlet pressure fixed at 0.1 MPa, inlet pressure adjusted to 0.30 MPa (pressure difference 0.2 MPa) and 0.70 MPa (pressure difference 0.6 MPa), respectively. The purity of the outlet hydrogen was determined using gas chromatography, and the hydrogen permeability coefficient was calculated. When the pressure difference is 0.2 MPa, the hydrogen permeability coefficient is 6.0~7.0×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0043] When the pressure difference is 0.6 MPa, the hydrogen permeability coefficient is 8.0~10.0×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0044] After 300 hours of continuous hydrogen permeation testing, the sample showed no significant deformation or cracking. The curve of hydrogen permeation coefficient versus pressure difference is shown below. Figure 3 As shown.
[0045] Example 2 Example 2 of the present invention prepares tantalum-niobium carbide ceramic-palladium composite foil according to the following steps: (1) Preparation of niobium carbide gradient ceramics Tantalum metal foil with a purity of 99.95% and a thickness of 350μm was used. After plasma surface cleaning for 30 minutes, a niobium metal nanolayer was deposited by magnetron sputtering for 8 minutes.
[0046] The material was placed in a tube furnace and purged with an oxygen atmosphere (oxygen flow rate of 60 mL / min) and heat-treated at 100°C for 40 minutes to form a niobium oxide ceramic nanolayer with a thickness of approximately 150–350 nm. Subsequently, graphite was deposited by magnetron sputtering for 15 minutes to form a graphite layer with a thickness of approximately 300 nm.
[0047] The sample was transferred to a vacuum tube furnace and heated to 1350°C at a heating rate of 3°C / min. The temperature was held for 2 hours to generate a porous niobium carbide ceramic gradient layer with a thickness of about 300~400nm.
[0048] Scanning electron microscope images of the obtained tantalum-niobium carbide ceramic composite material are shown below. Figure 4 As shown. Figure 4 In the medium, niobium carbide particles are uniform in size, with interconnected pores and a porosity of about 30%, which meets the requirements for hydrogen diffusion channels.
[0049] (2) Preparation of palladium catalyst layer After plasma cleaning of the niobium carbide ceramic gradient layer (argon flow rate 35 mL / min, cleaning time 10 min), palladium metal was deposited by magnetron sputtering for 20 min to form a palladium catalytic layer with a thickness of about 200 nm, thus obtaining a tantalum-niobium carbide ceramic-palladium composite foil.
[0050] Scanning electron microscope images of the obtained composite material are as follows: Figure 5 As shown, Figure 5 In the middle, the palladium layer and the niobium carbide layer are tightly bonded at the interface without gaps.
[0051] (3) Hydrogen permeability test of composite foil Following the test method in Example 1, a hydrogen permeation test was performed at 500°C. When the pressure difference is 0.2 MPa, the hydrogen permeability coefficient is 5.5~6.5×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0052] When the pressure difference is 0.6 MPa, the hydrogen permeability coefficient is 8.5~9.5×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0053] After 300 hours of continuous hydrogen permeation, the sample structure remained intact, and its resistance to hydrogen embrittlement was stable. The curve showing the change of the hydrogen permeation coefficient with pressure difference is as follows: Figure 6 As shown.
[0054] Example 3 Example 3 of the present invention prepares tantalum-niobium carbide ceramic-palladium composite foil according to the following steps: (1) Preparation of niobium carbide gradient ceramics Tantalum metal foil with a purity of 99.99% and a thickness of 500μm was used. After plasma surface cleaning for 30 minutes, a niobium metal nanolayer was deposited by magnetron sputtering for 10 minutes.
[0055] The material was placed in a tube furnace and purged with an oxygen atmosphere (oxygen flow rate of 40 mL / min) and heat-treated at 100°C for 50 minutes to form a niobium oxide ceramic nanolayer with a thickness of approximately 200–350 nm. Subsequently, graphite was deposited by magnetron sputtering for 20 minutes to form a graphite layer with a thickness of approximately 500 nm.
[0056] The sample was transferred to a vacuum tube furnace and heated to 1500℃ at a heating rate of 5℃ / min, and held for 3 hours to generate a porous niobium carbide ceramic gradient layer with a thickness of about 400~500nm.
[0057] Scanning electron microscope images of the obtained tantalum-niobium carbide ceramic composite material are shown below. Figure 7 As shown. Figure 7 In the middle layer, the niobium carbide has a complete porous structure with uniform pore size and no obvious agglomeration. Even when the layer thickness reaches the upper limit of the design, it still maintains good porosity.
[0058] (2) Preparation of palladium catalyst layer After plasma cleaning of the niobium carbide ceramic gradient layer (argon flow rate 25 mL / min, cleaning time 10 min), palladium metal was deposited by magnetron sputtering for 30 min to form a palladium catalytic layer with a thickness of about 300 nm, thus obtaining a tantalum-niobium carbide ceramic-palladium composite foil.
[0059] Scanning electron microscope images of the obtained composite material are as follows: Figure 8 As shown. Figure 8 In this study, the palladium catalyst layer exhibits good density and is free of pinhole defects, while the interfacial bonding strength between it and the niobium carbide layer meets the requirements for industrial use.
[0060] (3) Hydrogen permeability test of composite foil Following the test method in Example 1, a hydrogen permeation test was performed at 500°C. When the pressure difference is 0.2 MPa, the hydrogen permeability coefficient is 5.0~6.0×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0061] When the pressure difference is 0.6 MPa, the hydrogen permeability coefficient is 9.0~10.0×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 .
[0062] After 300 hours of continuous hydrogen permeation, the sample showed no brittleness or performance degradation, and the stability of the hydrogen permeation coefficient was superior to that of similar materials in the industry. The curve of the hydrogen permeation coefficient changing with pressure difference is shown below. Figure 9 As shown.
[0063] Examples 1-3 of this invention all achieve the following characteristics of tantalum-niobium carbide ceramic-palladium composite foil: Structural stability: The niobium carbide ceramic gradient layer (porous structure) effectively blocks the interdiffusion of tantalum and palladium metals, and no interlayer delamination was observed after a 300-hour hydrogen permeability test.
[0064] Hydrogen embrittlement resistance: The high mechanical strength of niobium carbide ceramics and the hydrogen permeability of tantalum metal work synergistically. Under a high pressure difference of 0.6 MPa at 500℃, no hydride is generated in the material, and no cracks are found after 50 bending tests (bending radius of 10 mm). High hydrogen permeability selectivity: The hydrogen permeability coefficient remains consistently between 5.0 and 10.0 × 10⁻⁶ at 500℃ and a pressure difference of 0.2–0.6 MPa. - 8 mol·m -1 ·s -1 ·Pa -0.5 The hydrogen purity is >99.999%, and the impurity (N2, CO2) rejection rate is >99.5%.
[0065] Furthermore, the tantalum-niobium carbide ceramic-palladium composite foil prepared based on the above embodiments can be assembled with graphite paper rings or silver rings to form a high-purity hydrogen separation foil material, which can be directly used as the core separation element of a hydrogen purifier. It exhibits excellent industrial applicability in scenarios such as the purification of chemical by-product hydrogen and the preparation of hydrogen for fuel cells.
[0066] The present invention also provides a material for hydrogen separation, comprising the tantalum-niobium carbide ceramic-palladium composite foil as described in any of the preceding claims, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by any of the preceding claims.
[0067] The present invention also provides the use of the tantalum-niobium carbide ceramic-palladium composite foil as described in any of the preceding claims, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by the preparation method described in any of the preceding claims, in the preparation of a purification membrane for hydrogen separation.
[0068] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0069] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0070] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A tantalum-niobium carbide ceramic-palladium composite foil, characterized in that, include: Tantalum metal layer; Niobium carbide ceramic gradient layers are formed on both sides of the tantalum metal layer, and the niobium carbide ceramic gradient layers have a porous structure. And a palladium catalyst layer deposited on the surface of the niobium carbide ceramic gradient layer.
2. The tantalum-niobium carbide ceramic-palladium composite foil according to claim 1, characterized in that, The tantalum metal layer has a purity of 99.90–99.99% and a thickness of 200–500 μm; the niobium carbide ceramic gradient layer has a thickness of 100–500 nm; and the palladium catalyst layer has a thickness of 100–300 nm.
3. The tantalum-niobium carbide ceramic-palladium composite foil according to claim 1 or 2, characterized in that, The hydrogen permeability coefficient of the composite foil is 5.0 × 10⁻⁶ under conditions of 500°C and a pressure difference of 0.2 MPa. -8 ·mol·m -1 ·s -1 ·Pa -0.5 ~7.0×10 -8 mol·m -1 ·s -1 ·Pa -0.5 The hydrogen permeability coefficient under conditions of 500℃ and a pressure difference of 0.6MPa is 8.0×10⁻⁶. -8 mol·m -1 ·s -1 ·Pa -0.5 ~10.0×10 -8 mol·m -1 ·s -1 ·Pa -0.5 .
4. A method for preparing a tantalum-niobium carbide ceramic-palladium composite foil as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Preparation of niobium carbide gradient ceramics, including: A niobium metal nanolayer is deposited on the surface of tantalum foil by magnetron sputtering, followed by heat treatment in an oxygen atmosphere to form a niobium oxide ceramic nanolayer; then a graphite layer is deposited on the surface of the niobium oxide ceramic; finally, a porous niobium carbide ceramic gradient layer is formed by heat treatment at 1200-1500℃ for 1-3 hours in a vacuum atmosphere with a heating rate of 1-5℃ / min. (2) Preparation of a palladium catalyst layer, including: The porous niobium carbide ceramic layer is subjected to plasma cleaning, and then a palladium layer is deposited on its surface by magnetron sputtering to form a palladium catalytic layer with a thickness of 100-300 nm, thereby obtaining the tantalum-niobium carbide ceramic-palladium composite foil.
5. The preparation method according to claim 4, characterized in that, In step (1), the thickness of the graphite layer is 100-500 nm.
6. A material for hydrogen separation, characterized in that, It includes the tantalum-niobium carbide ceramic-palladium composite foil as described in any one of claims 1 to 3, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by the preparation method described in any one of claims 4 to 5.
7. The use of the tantalum-niobium carbide ceramic-palladium composite foil as described in any one of claims 1 to 3, or the tantalum-niobium carbide ceramic-palladium composite foil prepared by the preparation method as described in any one of claims 4 to 5, in the preparation of a purification membrane for hydrogen separation.